Saman taivaan alla / Under samma himmel 1. - von Bonsdorff, Pauline; Jaukkuri, Maaretta; Numminen, M. A. (Helsinki : KIASMA Museum of Contemporary Art, 1999)
Summer 1999-2000 The Museum of Contemporary Art Kiasma is arranging an urban art project as part of Helsinki European City of Culture 2000. This year long international exhibition will be staged in four different parts of Helsinki. under the same sky will focus on the multilayered character of contemporary urban art and especially on viewing situations in the differing contexts of everyday life, under a wide range of climatic conditions, as an experience shared by both artists and spectators.
biog., tent.. p. 84-87
Engels & Fins
Saman taivaan alla / Under samma himmel / Under the same sky 1, Kallio / Berghäll, 1.9. - 30.11.1999, KIASMA (Museum of Contemporary Art) Helsinki
boek
Keywords: Brinch, Jes; Plenge Jakobsen, Henrik; Heikinaho, Minna; Viola, Bill; Wirkkala, Maaria; Finland; Helsinki